A maladaptive pleural environment suppresses preexisting anti-tumor activity of pleural infiltrating T cells - Donnenberg, Vera S.; Luketich, James D.; Sultan, Ibrahim; Lister, John; Bartlett, David L.; Ghosh, Sohini; Donnenberg, Albert D. (Frontiers in Immunology, 2023)
Background. Treatment options for patients with malignant pleural effusions (MPE) are limited due, at least in part, to the unique environment of the pleural space, which drives an aggressive tumor state and governs the behavior of infiltrating immune cells. Modulation of the pleural environment may be a necessary step toward the development of effective treatments. We examine immune checkpoint molecule (ICM) expression on pleural T cells, the secretomes of pleural fluid, pleural infiltrating T cells (PIT), and ability to activate PIT ex vivo. Methods. ICM expression was determined on freshly drained and in vitro activated PIT from breast, lung and renal cell cancer. Secretomics (63 analytes) of activated PIT, primary tumor cultures and MPE fluid was determined using Luminex technology. Complementary digital spatial proteomic profiling (42 analytes) of CD45+ MPE cells was done using the Nanostring GeoMx platform. Cytolytic activity was measured against autologous tumor targets. Results. ICM expression was low on freshy isolated PIT; regulatory T cells (T-reg) were not detectable by GeoMx. In vitro activated PIT coexpressed PD-1, LAG-3 and TIGIT but were highly cytotoxic against autologous tumor and uniquely secreted cytokines and chemokines in the > 100 pM range. These included CCL4, CCL3, granzyme B, IL-13, TNFα, IL-2 IFNγ, GM-CSF, and perforin. Activated PIT also secreted high levels of IL-6, IL-8 and sIL-6Rα, which contribute to polarization of the pleural environment toward wound healing and the epithelial to mesenchymal transition. Addition of IL-6Rα antagonist to cultures reversed tumor EMT but did not alter PIT activation, cytokine secretion or cytotoxicity. Conclusions. Despite the negative environment, immune effector cells are plentiful, persist in MPE in a quiescent state, and are easily activated and expanded in culture. Low expression of ICM on native PIT may explain reported lack of responsiveness to immune checkpoint blockade. The potent cytotoxic activity of activated PIT and a proof-of-concept clinical scale GMP-expansion experiment support their promise as a cellular therapeutic. We expect that a successful approach will require combining cellular therapy with pleural conditioning using immune checkpoint blockers together with inhibitors of upstream master cytokines such as the IL-6/IL-6R axis.